“Tomaschower Amtliche Zeitung” (1915–1917) as a historical source - Wojniłowicz, Jerzy (Acta Universitatis Lodziensis. Folia Germanica, 2020)
“Gazeta Urzędowa Tomaszowska” (“Tomaschower Amtliche Zeitung”) was an organ of the Municipality of Tomaszów Mazowiecki. It appeared twice a week from December 1915 to June 1917. The magazine was printed in German and Polish. It contained ordinances and announcements of the occupying central and local authorities, as well as semi-official and private announcements. In total, 160 issues of the magazine were published. The article discusses the content of TAZ, emphasizing the undeniable historical value of the magazine for the history of Tomaszów Mazowiecki during the First World War.